Guaranteeing Women’s Freedom under the Constitution: Gender Analysis of Qânûn Practices in Aceh - Anggriani, Jum; Abdullah, Ali; Cahyawati, Dwi Putri; Dahlan, Ahmad; Fahriani, Ipak (De Jure: Jurnal Hukum dan Syari'ah, 2025)
This article analyses and critiques the practice of qânûn in Aceh on guaranteeing women's freedom. Research data were collected from library research, including primary data obtained from scientific publications in journals, books, and proceedings on six qânûn documents in Aceh; secondary data consist of laws and regulations. The data were also gathered from interviews with Acehnese figures who were familiar with qânûn, Islamic law, and Acehnese customs. The analysis method refers to a descriptive-qualitative approach that combines doctrinal-normative and socio-legal analysis. The results show that all qânûn in Aceh are normatively valid legal products, as the Regional People's Representative Council ratifies them. However, their formulation and ratification reveal gender bias, as only 5% of female legislators have been involved, and in some regions, the percentage of female members remains at 0% until 2024. In its implementation, gender bias is also considered to be obvious, particularly in the application of caning punishment in public places, which gives social pressure on women, leaving women's interests not fully affirmed. The interviews with Acehnese figures suggest that qânûn is essentially a recognition of the synergy having existed since ancient times, when Aceh was still a kingdom where Islamic law and customary practices in Acehnese society placed women in policymaking roles.